Gatunki tekstów odnoszących się do przyszłości - Żmigrodzka, Bożena (Stylistyka, 2021)
The paper deals with a group of text genres in contemporary Polish, like prognoza (fo- recast), przepowiednia, proroctwo (prophecy), augury (wróżba) and horoskop (horoscope). These genres are deeply set in culture and their specifity is perfectly identified in so- cial linguistic conciousness. The most generał definition of the five genres can be as fol- lows: „I know that Y will happen/1 say this because I think you want to know, what will hapen”. The two characteristic features of these genres are: 1) all events presented are si- tuated in the futurę, after the act of lingual performance of these text; 2) primarily infor- mational character ot texts.All these genres, being assertives referring to the futurę, can be called „predictional genres”. Even though they have their roots in magie and religion, nowadays they func- tion also in other parts of social life, i.e. in science and popular culture. Prophecy, horo- scope and augury in magie orastrology have mostly informatic and therapeutic functions. When they occur in popular culture, the ludic function plays a part, and the informatical funtion is suspended.